Size-Dependent Tax Enforcement and Compliance : Global Evidence and Aggregate Implications - Bachas, Pierre (World Bank, Washington, DC, 2018)
This paper studies the prevalence and consequences of size-dependent tax enforcement and compliance. The identification strategy uses the ranking of industries' average firm size in the United States as an instrument for the size ranking of the same industries in developing countries. Data on 125,000 firms in 140 countries show that tax enforcement and compliance increase with size. Size-dependence is more prevalent in low-income countries, and concentrated at the top of the size distribution. When quantified in a general equilibrium model, removing size dependent enforcement leads to gains in Total Factor Productivity of up to 0.8 percent.